Spontaneous esophageal rupture as the underlying cause of pneumothorax: early recognition is crucial - Garas, George; Zarogoulidis, Paul; Efthymiou, Alkiviadis; Athanasiou, Thanos; Tsakiridis, Kosmas; Mpaka, Sofia; Zacharakis, Emmanouil (Journal of Thoracic Disease; Vol 6, No 12 (December 31, 2014): Journal of Thoracic Disease, 2014)
Boerhaave’s syndrome (BS), also known as “spontaneous rupture of the esophagus”, constitutes an emergency that requires early diagnosis if death or serious morbidity are to be prevented. First described in 1724, BS is thought to be more common than once thought. Its true incidence remains unknown. Mortality ranges between 20-40% with timely treatment but this rises to virtually 100% if treatment is delayed by more than 48 hours. This is unfortunately a common occurrence due to delayed diagnosis. The commonest precipitating factor is vomiting but BS can be truly “spontaneous”. The classical clinical presentation described consists of vomiting, chest pain, and subcutaneous emphysema. However, and contrary to popular belief, this triad is actually uncommon accounting for the frequently delayed diagnosis. A less recognised presenting feature of BS is with pneumothorax due to associated rupture of the parietal pleura. Pneumothorax has been shown to be present in more than 20% of cases of BS-sometimes with a coexistent pleural effusion (hydropneumothorax). This article aims to raise awareness about pneumothorax as the sole initial presenting feature of BS and alert clinicians to consider BS in the differential diagnosis of any patient with respiratory symptoms and a recent history of vomiting.